Encalypta altunense S. Mamtimin & E. Sabiram sp. nov. (Encalyptaceae, Musci), a new moss species from Xinjiang, northwestern China - Esrayil, Sabiram; Sulayman, Mamtimin; Wang, Xiaorui (Phytotaxa, 2018)
Encalypta altunense S. Mamtimin & E. Sabiram (Encalyptaceae), a new moss species from Xinjiang Uygur Autonomous Region, northwestern China, is described and illustrated. Particularly distinctive features of the new species are: (1) 3–4 teeth formed by single cell at the leaf apex, (2) dorsiventral with dense five-pointed star or irregularly forked papillae of leaf cells, (3) peristome single, linearly lanceolate, usually joint at base pair-wise, with dense and large papillae, and (4) spores yellowish brown, with large papillae on distal surface. Comparisons with morphologically similar Encalypta species are also presented.